The Right Kind of Help? : Tax Incentives for Staying Small - Benedek, Dora (IMF Working Papers; Working Paper ;, 2017)
Some countries support smaller firms through tax incentives in an effort to stimulate job creation and startups, or alleviate specific distortions, such as financial constraints or high regulatory or tax compliance costs. In addition to fiscal costs, tax incentives that discriminate by firm size without specifically targeting R and D investment can create disincentives for firms to invest and grow, negatively affecting firm productivity and growth. This paper analyzes the relationship between size-related corporate income tax incentives and firm productivity and growth, controlling for other policy and firm-level factors, including product market regulation, financial constraints and innovation. Using firm level data from four European economies over 2001-13, we find evidence that size-related tax incentives that do not specifically target R and D investment can weigh on firm productivity and growth. These results suggest that when designing size-based tax incentives, it is important to address their potential disincentive effects, including by making them temporary and targeting young and innovative firms, and R and D investment explicitly.